Auxin/AID versus conventional knockouts: distinguishing the roles of CENP-T/W in mitotic kinetochore assembly and stability. Issue 1 (January 2016) - Wood, Laura; Booth, Daniel G.; Vargiu, Giulia; Ohta, Shinya; deLima Alves, Flavia; Samejima, Kumiko; Fukagawa, Tatsuo; Rappsilber, Juri; Earnshaw, William C.
Abstract : Most studies using knockout technologies to examine protein function have relied either on shutting off transcription (conventional conditional knockouts with tetracycline-regulated gene expression or gene disruption) or destroying the mature mRNA (RNAi technology). In both cases, the target protein is lost at a rate determined by its intrinsic half-life. Thus, protein levels typically fall over at least 1–3 days, and cells continue to cycle while exposed to a decreasing concentration of the protein. Here we characterise the kinetochore proteome of mitotic chromosomes isolated from a cell line in which the essential kinetochore protein CENP-T is present as an auxin-inducible degron (AID) fusion protein that is fully functional and able to support the viability of the cells. Stripping of the protein from chromosomes in early mitosis via targeted proteasomal degradation reveals the dependency of other proteins on CENP-T for their maintenance in kinetochores. We compare these results with the kinetochore proteome of conventional CENP-T/W knockouts. As the cell cycle is mostly formed from G1, S and G2 phases a gradual loss of CENP-T/W levels is more likely to reflect dependencies associated with kinetochore assembly pre-mitosis and upon entry into mitosis. Interestingly, a putative super-complex involving Rod-Zw10-zwilch (RZZ complex), Spindly, Mad1/Mad2 and CENP-E requires the function of CENP-T/W during kinetochore assembly for its stable association with the outer kinetochore, but once assembled remains associated with chromosomes after stripping of CENP-T during mitosis. This study highlights the different roles core kinetochore components may play in the assembly of kinetochores (upon entry into mitosis) versus the maintenance of specific components (during mitosis).